Distal Symmetric Polyneuropathy in Diabetes. Differences between Patients with and without Neuropathic Pain - Mondelli, M.; Aretini, A.; Baldasseroni, A. (Experimental and Clinical Endocrinology & Diabetes, 2012)
To demonstrate whether in distal symmetric polyneuropathy (DSPN) in diabetes there are differences between patients with and without neuropathic pain and whether pain is associated with demographic, clinical and electrophysiological variables.We prospectively enrolled 154 consecutive patients (mean age 67 years, 64% men) in an electromyography (EMG) lab. The differences were calculated between DSPN patients with (no.78) and without neuropathic pain (no.76) relating to age, sex, BMI, type, duration, treatment and complications of diabetes, HbA1c, type and duration of DSPN symptoms, DSPN clinical severity score (with Diabetic Neuropathic Index-DNI), electrophysiological findings of lower limb muscles and nerves.The differences between DSPN patients with and without pain included the presence of symptoms (burning and weakness), DNI score and neurographic findings of all nerves and neurogenic EMG. But in the logistic regression models enter only the following variables: DNI score, neurogenic EMG, and among symptoms “burning-.The presence of pain in DSPN is associated with DSPN clinical severity, neurogenic EMG and presence of “burning- symptom but not with demographic or neurographic findings, or diabetes related variables. Therefore, the neuropathic pain in DSPN does not associate with the degree of involvement of large diameter sensory fibres or diabetes severity.
Keywords: diabetes; distal symmetric polyneuropathy; painful peripheral neuropathy; diabetes complications; pain